The reproductive system of Osedax (Annelida, Siboglinidae): ovary structure, sperm ultrastructure, and fertilization mode - Katz, Sigrid (Invertebr Biol, 2013)
Osedax is a genus of siboglinid annelids in which the females live on dead vertebrate bones on the seafloor. These females have a posterior end that lies within the bone and contains the ovarian tissue, as well as the “roots” involved with bone degradation and nutrition. The males are microscopic and live as “harems” in the lumen of the gelatinous tube that surrounds the female trunk, well away from the ovary. Females are known to spawn fertilized primary oocytes, suggesting internal fertilization. However, little is known about sperm transfer, sperm storage, or the location of fertilization, and the morphology of the female reproductive system has not been described and compared with the reproductive systems of other siboglinids. A 3D-reconstruction of the ovisac of Osedax showed ovarian tissue with multiple lobes and mature oocytes stored in a “uterus” before being released through the single oviduct. The oviduct emerges as a gonopore on the trunk and travels along the trunk to finally open to the seawater as a thin cylindrical tube among the crown of palps. Light and transmission electron microscopy of mature Osedax sperm revealed elongate heads consisting of a nucleus with helical grooves occupied by mitochondria. In contrast to other Siboglinidae, Osedax sperm are not packaged into spermatophores or spermatozeugmata, and Osedax females lack a discrete region for sperm storage. Transmission electron microscopy and fluorescence microscopy allowed detection of sperm associated with ovarian tissue of the female ovisac of four different Osedax species. This provides the first evidence for the site of internal fertilization in Osedax. A heart body was found in the circulatory system, as seen in other siboglinids and some other annelids. The possible presence of nephridia in the anterior ovisac region was also documented. These morphological features provide new insights for comparing the regionalization of Osedax females in relation to other siboglinids.